Zinc-doped or pre-sodium / potassium-zinc-doped hard carbon negative electrode material and preparation method and application thereof

Through the preparation method of zinc-doped or pre-sodium/potassium zinc-doped hard carbon anode material, the structural and surface defects of hard carbon are optimized, and the problem of poor kinetic performance of hard carbon anode materials in sodium ion batteries is solved, achieving efficient sodium ion storage and stable cycling performance.

CN119674067APending Publication Date: 2025-03-21SHENGHONG KINETIC ENERGY TECH (TAIZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411832730.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Hard carbon anode material has problems with low initial Coulomb efficiency and sodium dendrites in sodium ion batteries, resulting in poor kinetic performance.

Method used

The preparation method of zinc-doped or pre-sodium/potassium zinc-doped hard carbon negative electrode materials is adopted, and the liquid phase and solid phase two-step method is prepared to optimize the graphite region and nanopore structure of hard carbon, reduce the defect content, and improve the hard carbon surface defects through pre-sodium or pre-potassium treatment.

Benefits of technology

The dynamic performance and cyclic performance of zinc-doped hard carbon anode material is significantly improved, the initial Coulomb efficiency is improved, and the optimal capacity and efficiency are maintained at high magnifications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674067A_ABST
    Figure CN119674067A_ABST
Patent Text Reader

Abstract

The invention provides a zinc-doped or pre-sodium / potassium-zinc-doped hard carbon negative electrode material as well as a preparation method and application thereof. The preparation method comprises the following steps: weighing 2, 4-diaminophenol and zinc salt, adding the 2, 4-diaminophenol and the zinc salt into a solvent, and uniformly stirring and mixing; adding a formaldehyde solution for water-bath heating and stirring reaction; and filtering, cleaning and drying the product to obtain a sample, mixing the sample with hard carbon particles, calcining at high temperature, and cooling to obtain the zinc-doped hard carbon negative electrode material. And further, carrying out sodium pre-treatment or potassium pre-treatment by adopting a DMC-Na or DMC-K solution to obtain the pre-sodium / potassium zinc doped hard carbon negative electrode material. The zinc-doped hard carbon negative electrode material has an expanded graphite region and highly developed nanopores, and is high in conductivity; after pre-sodium or pre-potassium treatment, hard carbon surface defects are remarkably improved, an SEI film is formed, side reaction between electrolyte and the hard carbon surface is further isolated, the dynamic performance of the material is remarkably improved, ICE is remarkably improved, and the cycle performance of the material is considered on the basis of dynamics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium-potassium ion batteries, and in particular relates to a zinc-doped or pre-sodium / potassium-zinc-doped hard carbon negative electrode material and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries (SIBs) are considered to be a promising and cost-effective electrochemical energy storage method for large-scale electrical energy storage and smart grid technology due to their abundant sodium resources. The electrochemical performance of SIB batteries depends on the electrode materials and their interface structure facing the electrolyte. Hard carbon (HC) has low cost, large specific capacity, and appropriate redox potential for sodium. Hard carbon is composed of curved, randomly oriented and defective carbon layers with five / seven-membered carbon rings and surface oxygen-containing functional groups such as hydroxyl and carboxyl groups, which can be used for large-radius Na + The hard carbon negative electrode material has obvious surface defects and is superior to the fracture and recombination of the solid electrolyte interface (SEI) of the negative electrode, which leads to low initial Coulomb efficiency (ICE) and even the generation of sodium dendrites. Therefore, in order to achieve stable sodium storage, the hard carbon negative electrode interface needs to be adjusted and modified to reduce side reactions and improve energy efficiency and cycle.

[0003] The formation of solid electrolyte interface (SEI) is caused by the inevitable decomposition of electrolyte at lower potentials during initial cycling (<1V). Excessive SEI accumulation consumes electrolyte, depletes available alkaline ions, and increases cell polarization throughout the cycling process. Non-SEI-related capacity losses due to irreversible adsorption of sodium at graphene defect sites and irreversible intercalation between graphene layers also contribute to low Coulombic efficiency in the first few cycles.

[0004] Therefore, it is urgent to provide a zinc-doped or pre-sodium / potassium-zinc-doped hard carbon negative electrode material to further improve the kinetic performance of the battery. Summary of the invention

[0005] Based on the defects of the prior art, the first purpose of the present invention is to provide a method for preparing a zinc-doped hard carbon negative electrode material; the second purpose of the present invention is to provide a zinc-doped hard carbon negative electrode material prepared by the preparation method; the third purpose of the present invention is to provide a method for preparing a pre-sodium / potassium-zinc doped hard carbon negative electrode material; the fourth purpose of the present invention is to provide a pre-sodium / potassium-zinc doped hard carbon negative electrode material prepared by the preparation method; the fifth purpose of the present invention is to provide the use of the zinc-doped hard carbon negative electrode material or the pre-sodium / potassium-zinc doped hard carbon negative electrode material in the preparation of sodium ion batteries or potassium ion batteries.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] In one aspect, the present invention provides a method for preparing a zinc-doped hard carbon negative electrode material, the preparation method comprising the following steps:

[0008] Step 1, weighing 2,4-diaminophenol and zinc salt, adding them to a solvent, and stirring to obtain a mixed solution;

[0009] Step 2, adding formaldehyde solution to the mixed solution, heating in a water bath and stirring to react; filtering, washing and drying the product to obtain a sample;

[0010] Step three, mixing the sample with hard carbon particles and calcining them at high temperature, and obtaining a zinc-doped hard carbon negative electrode material after cooling.

[0011] In the preparation method of the zinc-doped hard carbon negative electrode material of the present invention, the volume and surface structure are adjusted by using atomically bonded zinc atoms, and the optimized hard carbon has an enlarged graphite area (d002 = 0.408nm) and highly developed nanopores (diameter ≈ 0.8nm), and the defect content is reduced, which is conducive to the rapid storage of Na + .

[0012] In the above preparation method, preferably, in step 1, the zinc salt is selected from a combination of one or more of zinc acetate, zinc citrate, zinc sulfate, zinc nitrate and zinc perchlorate; but not limited thereto.

[0013] In the above preparation method, preferably, in step 1, the solvent is a mixed solvent of deionized water and anhydrous ethanol; preferably, the volume ratio of the two is 1:1.

[0014] In the above preparation method, preferably, in step 1, the mass ratio of the 2,4-diaminophenol to the zinc salt is 3:1 to 10:1.

[0015] In the above preparation method, preferably, in step 1, the concentration of 2,4-diaminophenol in the mixed solution is 0.2-0.3 mol / L.

[0016] In the above preparation method, preferably, in step 1, the concentration of the zinc salt in the mixed solution is 0.02-0.05 mol / L.

[0017] In the above preparation method, preferably, in step 2, the mass of the formaldehyde solution is 2 / 3 to 1 times the mass of the 2,4-diaminophenol.

[0018] In the above preparation method, preferably, in step 2, the formaldehyde solution is a 30% to 40% formaldehyde aqueous solution.

[0019] In the above preparation method, preferably, in step 2, the temperature for the water bath heating and stirring reaction is 60-70° C.; and the reaction time is 2-8 h.

[0020] In the above preparation method, preferably, the filtration is performed by centrifugation to remove the supernatant; and the washing is performed by anhydrous ethanol at least 3 times.

[0021] In the above preparation method, preferably, the drying temperature is 80 to 110° C. and the drying time is 12 to 24 hours.

[0022] In the above preparation method, preferably, in step three, the mass of the hard carbon particles is 5 to 40 times that of the zinc salt.

[0023] In the above preparation method, preferably, in step three, the temperature of the high temperature calcination is 900-1500° C., and the calcination time is 1-4 hours.

[0024] In the above preparation method, preferably, in step three, high temperature calcination is carried out in an inert gas atmosphere, and the inert gas is selected from one or more of argon, helium and nitrogen.

[0025] On the other hand, the present invention also provides a zinc-doped hard carbon negative electrode material, which is prepared by the above-mentioned preparation method.

[0026] In another aspect, the present invention further provides a method for preparing a pre-sodium / potassium-zinc doped hard carbon negative electrode material, the preparation method comprising the following steps:

[0027] Step 1, adding degassed mineral oil to a sodium block or a potassium block for ultrasonic pulse heating to dissolve and form liquid sodium; uniformly dispersing the liquid sodium or liquid potassium in the mineral oil by ultrasonic oscillation; further dispersing the substrate obtained by centrifugation in a dimethyl carbonate solution to obtain a DMC-Na or DMC-K solution;

[0028] Step 2, mixing the zinc-doped hard carbon negative electrode material with conductive carbon black and sodium carboxymethyl cellulose in an N-methylpyrrolidone solution to obtain a mixed solution, coating the mixed solution on a copper foil, and cutting the mixed solution into zinc-doped hard carbon negative electrode small discs after air drying and vacuum drying again;

[0029] Step 3, adding DMC-Na or DMC-K solution to the surface of zinc-doped hard carbon negative electrode small disc for diffusion reaction, after DMC-Na or DMC-K solution is completely diffused on the surface of the small disc, a pre-sodium / potassium-zinc doped hard carbon negative electrode material is obtained.

[0030] Furthermore, the present invention proposes a pre-sodium / potassium zinc-doped hard carbon negative electrode material based on the zinc-doped hard carbon negative electrode material, that is, by dissolving a sodium block or a potassium block into a single particle of sodium or potassium, and then rolling it into a hard carbon negative electrode. The hard carbon negative electrode prepared by this method has better kinetic performance, and after pre-sodium or pre-potassium, its ICE is significantly improved, taking into account its cycle performance on the basis of kinetics.

[0031] In the above preparation method, preferably, in step 1, the mass fraction of the sodium block or potassium block in the mineral oil is 0.5% to 1%.

[0032] In the above preparation method, preferably, in step 1, the mineral oil is degassed by ultrasonic method in an inert gas atmosphere; the degassing time is 10 to 30 minutes; and the inert gas is selected from one or more of argon, helium and nitrogen.

[0033] In the above preparation method, preferably, in step 1, the ultrasonic pulse heating temperature is 90-110°C, the heating time is 0.5-5min, the stop time is 10s-60s, the heating-standing times are 10-20 times; and the ultrasonic oscillation time is 5-30min.

[0034] In the above preparation method, preferably, in step 1, the volume of the N-methylpyrrolidone solution is 0.5 to 0.8 times the volume of the mineral oil.

[0035] In the above preparation method, preferably, in step 2, the mass ratio of the zinc-doped hard carbon negative electrode material to the conductive carbon black and the sodium carboxymethyl cellulose is 8:1:1; and the solid content of the mixed solution is 50% to 70%.

[0036] In the above preparation method, preferably, in step 2, the air drying temperature is 80-110° C.; the air drying time is 0.5-3 h; the vacuum drying temperature is 20-30° C.; and the vacuum drying time is 1-4 h.

[0037] In the above preparation method, preferably, in step 3, the amount of the DMC-Na or DMC-K solution added is 5 to 15 μL, and the diffusion reaction time is 1 to 5 min.

[0038] On the other hand, the present invention also provides a pre-sodium / potassium-zinc doped hard carbon negative electrode material, which is prepared by the preparation method described in claim 7 or 8.

[0039] On the other hand, the present invention also provides the use of the above-mentioned zinc-doped hard carbon negative electrode material, or the above-mentioned pre-sodium / potassium-zinc-doped hard carbon negative electrode material in the preparation of sodium ion batteries or potassium ion batteries.

[0040] Beneficial effects of the present invention:

[0041] (1) The preparation method of the zinc-doped hard carbon negative electrode material of the present invention adopts a two-step process of liquid phase and solid phase, and the overall operation time is within 24 hours, and the process time is short; the prepared zinc-doped hard carbon negative electrode material has an enlarged graphite area (d002 = 0.408nm) and highly developed nanopores (diameter ≈ 0.8nm), and the defect content is reduced, which is conducive to the rapid storage of Na + The negative electrode material has large internal pore size and strong conductivity.

[0042] (2) The present invention further performs pre-sodium or pre-potassium treatment on the zinc-doped hard carbon negative electrode material, which significantly improves the surface defects of the hard carbon and forms a SEI film to further isolate the side reactions between the electrolyte and the hard carbon surface. The prepared pre-sodium / potassium-zinc doped hard carbon negative electrode material significantly improves the kinetic performance, and its ICE is significantly improved. On the basis of kinetics, its cycle performance is taken into account. It is particularly suitable for sodium ion battery (SIB) and potassium ion battery (KIB) systems, and still has better capacity and efficiency at high rates.

[0043] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0045] Figure 1 This is a schematic diagram of the process of preparing zinc-doped hard carbon negative electrode material and pre-sodium-zinc-doped hard carbon negative electrode material in Example 1 of the present invention.

[0046] Figure 2 The scanning electron microscope microstructure and EDS comparison diagram of the zinc-doped hard carbon negative electrode material (HC&Zn) prepared in Example 1 of the present invention and the conventional hard carbon material (HC).

[0047] Figure 3 This is a comparison chart of the nitrogen adsorption amount of the pre-sodium-zinc doped hard carbon negative electrode material (HC&Zn-Na) prepared in Example 1 of the present invention and the conventional hard carbon material (HC).

[0048] Figure 4Comparison chart of charge and discharge curves and discharge capacity of the pre-sodium-zinc doped hard carbon negative electrode material (HC&Zn-Na) prepared in Example 1 of the present invention and the conventional hard carbon material (HC).

[0049] Figure 5 This is a comparison chart of the cycle performance of the pre-sodium-zinc doped hard carbon negative electrode material (HC&Zn-Na) prepared in Example 1 of the present invention and the conventional hard carbon material (HC). DETAILED DESCRIPTION

[0050] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The process, conditions, reagents, experimental methods, etc. for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and common common sense in the art, and the present invention does not particularly limit the contents.

[0051] Embodiment 1:

[0052] This embodiment provides a method for preparing a zinc-doped hard carbon negative electrode material (HC&Zn), such as Figure 1 As shown, the preparation method comprises the following steps:

[0053] (1) Weigh 3 g of 2,4-diaminophenol (2,4-DAP) and 0.5 g of zinc acetate (ZnAc2) and add them to 100 mL of a mixed solvent of anhydrous ethanol and deionized water (the volume ratio of deionized water to anhydrous ethanol is 1:1), and stir to obtain a mixed solution.

[0054] (2) Add 3 mL of formaldehyde solution to the mixed solution, then place the mixed solution in a 65° C. water bath and stir to perform polymerization for 4 h, and remove the supernatant by centrifugation.

[0055] (3) The mixed solution was then washed with anhydrous ethanol for three times (20 mL of anhydrous ethanol was added each time, and then the supernatant was removed after centrifugation for 10 min, leaving the bottom precipitate), and the precipitate was placed in a 90° C. forced air oven and dried for 12 h before taking out the sample.

[0056] (4) The dried sample and 10 g of hard carbon particles were mixed evenly and then placed in a high-temperature furnace at 1300°C for calcination. Argon was flushed into the cavity during calcination. The addition was stopped after calcination for 2 hours. The sample was taken out after cooling, thus obtaining a zinc-doped hard carbon material, which was recorded as: HC&Zn.

[0057] This embodiment also provides a method for preparing a pre-sodium zinc doped hard carbon negative electrode material (HC&Zn-Na), such as Figure 1As shown, the preparation method comprises the following steps:

[0058] (1) Take 20 mL of mineral oil, then put it into an ultrasonic processor for degassing for 30 minutes, and then flush it with argon (operate in a glove box); then add 120 mg of sodium block to the degassed mineral oil, then start ultrasonic pulse heating, heat for 1 minute and then stand for 30 seconds. After repeating this for about 15 times, it can be seen that the solid sodium block gradually dissolves into liquid sodium. At this time, the temperature of the mixed solution is about 100°C; then start the ultrasonic oscillation mode to evenly disperse the liquid sodium in the mineral oil, and then after centrifugation, obvious stratification can be seen, remove the upper mineral oil, and wash the bottom material with dimethyl carbonate solution (DMC) at least 3 times (add 20 mL of DMC each time, then centrifuge for 10 minutes to remove the upper mineral oil, leaving the bottom material); the obtained bottom material is dispersed in 20 mL of dimethyl carbonate solution to obtain DMC-Na solution.

[0059] (2) 10 g of the zinc-doped hard carbon material (HC&Zn), conductive carbon black (SP) and sodium carboxymethyl cellulose (CMC) prepared above were weighed in a mass ratio of 8:1:1, and N-methylpyrrolidone solution (NMP) was added to disperse and adjust the solid content to 60%. Then, the mixture was dispersed at 600 rpm for 5 min and then the speed was adjusted to 2000 rpm for high-speed dispersion for 30 min to obtain a mixed slurry; the mixed slurry was then coated on a copper foil with a 200 μm scraper, and then dried in a blast drying oven at 110°C for 1 h and then taken out to obtain a hard carbon negative electrode sheet; the dried hard carbon negative electrode sheet was punched into a 14 mm small disc with a punching machine, and then vacuum dried at room temperature for 2 h and then taken out to prepare a HC&Zn hard carbon small disc, and then the small disc was placed in a glove box for standby use.

[0060] (3) The HC&Zn hard carbon disc prepared in step (2) is placed in a glass crucible, and then 10 mL of the DMC-Na solution prepared in step (1) is dripped onto the surface of the active material, and the solution is allowed to diffuse. After standing for about 3 min, the target product can be obtained after the surface is completely diffused, which is a pre-sodium-zinc doped hard carbon negative electrode material, denoted as: HC&Zn-Na.

[0061] This embodiment also provides a method for assembling a sodium ion battery using the pre-sodium zinc doped hard carbon negative electrode material (HC&Zn-Na) prepared above, and the specific method is as follows:

[0062] (1) The HC&Zn-Na material prepared in the above embodiment was sliced ​​and vacuum dried in accordance with the buckle battery assembly procedure, and then assembled in a glove box (with a water content of <1ppm and an oxygen content of <1ppm); an electrolyte was added during the assembly process, and the electrolyte was a 1.0M NaLiF6 DMC solution. During the assembly test, the HC&Zn-Na material was used as the positive electrode and the sodium sheet was used as the negative electrode. The assembled buckle battery was sealed and activated at 35°C for 12 hours to prepare a sodium ion buckle battery.

[0063] Comparative Example 1:

[0064] This comparative example provides a method for assembling a sodium ion battery using a conventional hard carbon electrode sheet as a negative electrode material, and the specific method is as follows:

[0065] (1) Conventional untreated hard carbon particles were used, and a total of 10 g of them were weighed with conductive carbon black (SP) and sodium carboxymethyl cellulose (CMC) in a mass ratio of 8:1:1. NMP was added to disperse and the solid content was adjusted to 60%. Then, the mixture was dispersed at 600 rpm for 5 min and then the speed was adjusted to 2000 rpm for high-speed dispersion for 30 min to obtain a mixed slurry. The mixed slurry was then coated on a copper foil with a 200 μm scraper, and then dried in a blast drying oven at 110° C. for 1 h and then taken out to obtain a hard carbon negative electrode sheet. The dried hard carbon negative electrode sheet was punched into a 14 mm small disc with a sheet puncher, and then vacuum dried at room temperature for 2 h and then taken out to prepare an HC hard carbon small disc.

[0066] (2) The HC hard carbon discs prepared in the above (1) were sliced ​​and vacuum dried in accordance with the buckle battery assembly procedure, and then put into a glove box (with a water content of <1ppm and an oxygen content of <1ppm) for assembly; an electrolyte was added during the assembly process, and the electrolyte was a 1.0M NaLiF6 DMC solution. During the assembly test, the HC material was used as the positive electrode and the sodium sheet was used as the negative electrode. The assembled buckle battery was sealed and activated at 35°C for 12h to prepare a sodium ion buckle battery.

[0067] Test experiment:

[0068] The sodium ion buckling prepared in Example 1 and Comparative Example 1 of the present invention was tested for buckling performance, and the specific test process is as follows:

[0069] Stand for 2h→rate discharge 0.1C, voltage ≤0.005v→constant current discharge 0.05mA, voltage ≤0.005v→constant current discharge 0.02mA, voltage ≤0.005v→stand for 10min→rate charge 0.1C, voltage ≥2V

[0070] Test results such as Figure 2 to Figure 4 shown.

[0071] Figure 2 The scanning electron microscope microstructure and EDS comparison diagram of the zinc-doped hard carbon negative electrode material (HC&Zn) prepared in Example 1 of the present invention and the conventional hard carbon material (HC); Figure 2 (a) shows the microscopic morphology and EDS image of HC&Zn materials; Figure 2 (b) in the figure shows the microscopic morphology and EDS image of the HC material.

[0072] Depend on Figure 2 It can be seen that the particles of Zn-doped hard carbon material are obviously larger. This is because the radius of Zn atoms is larger. After being inserted between the hard carbon layers, the distance between the layers will increase, thereby further increasing the overall radius. From the element distribution diagram of EDS, it can be seen that the HC&Zn material has obvious element distribution diagrams of C, N, O and Zn, while the HC material only has C, N and O elements distributed, further indicating that the Zn element has been embedded in the hard carbon layers.

[0073] Figure 3 This is a comparison chart of the nitrogen adsorption amount of the pre-sodium-zinc doped hard carbon negative electrode material (HC&Zn-Na) prepared in Example 1 of the present invention and the conventional hard carbon material (HC).

[0074] Depend on Figure 3 It can be seen that: under different relative pressures, the amount of nitrogen adsorbed on the surface of HC&Zn-Na material is less than that of HC material, indicating that after pre-sodiumization, the hard carbon material has significantly fewer surface defects and its corresponding surface area is smaller. However, due to the addition of Zn into the hard carbon, the particle size becomes larger, and its surface area will increase to a certain extent. By calculation, the surface areas of HC&Zn-Na material and HC material are 1.44m 2 / g and 1.52m 2 / g, the difference between the before and after materials is small.

[0075] Figure 4 A comparison diagram of the charge-discharge curves and discharge capacity of the pre-sodium-zinc doped hard carbon negative electrode material (HC&Zn-Na) prepared in Example 1 of the present invention and the conventional hard carbon material (HC); Figure 4 (a) is a comparison of the charge and discharge curves of HC&Zn-Na material and HC material; Figure 4 (b) is a comparison chart of the discharge capacities of HC&Zn-Na materials and HC materials.

[0076] Depend on Figure 4 It can be seen that: Figure 4As can be seen in (a), the HC&Zn-Na material has a higher capacity due to its surface pre-sodium treatment and internal doping with Zn. At a rate of 0.05C, the HC&Zn-Na material has a capacity of 623mAh / g, while the HC material has a capacity of only 363mAh / g. The HC&Zn-Na material has an initial efficiency of 95.5%, while the HC material has an initial efficiency of only 73%, further illustrating the improvement of the material system by Zn doping and pre-sodium treatment. Figure 4 As can be seen in (b), with the increase of rate, the performance of HC&Zn-Na material and HC material both decreases, mainly due to their kinetic factors. However, HC&Zn-Na material has obvious advantages over HC material. At the same rate, HC&Zn-Na material is much better than HC material. At 10C rate, HC&Zn-Na has a capacity of 335mAh / g, while HC material has a capacity of only 102mAh / g.

[0077] Figure 5 This is a comparison chart of the cycle performance of the pre-sodium-zinc doped hard carbon negative electrode material (HC&Zn-Na) prepared in Example 1 of the present invention and the conventional hard carbon material (HC).

[0078] Depend on Figure 5 It can be seen that the cycle performance and efficiency of HC&Zn-Na material are significantly better than those of HC material. HC&Zn-Na material has excellent cycle stability. After 6000 cycles, its capacity is about 295mAh / g, and its capacity retention rate is 82.4%. After 6000 cycles, the capacity of HC material is 152mAh / g, and its retention rate is only 59.3%. This further illustrates that during the cycle process, the SEI film structure of HC&Zn-Na material is stable and not easily damaged, while the HC material continuously experiences SEI film damage and reconstruction during the whole process, resulting in irreversible Na loss, so its capacity and efficiency are significantly lower.

[0079] The present invention uses specific embodiments to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A method for preparing a zinc-doped hard carbon negative electrode material, characterized in that: The preparation method comprises the following steps: Step 1, weighing 2,4-diaminophenol and zinc salt, adding them to a solvent, and stirring to obtain a mixed solution; Step 2, adding formaldehyde solution to the mixed solution, heating in a water bath and stirring to react; filtering, washing and drying the product to obtain a sample; Step three, mixing the sample with hard carbon particles and calcining them at high temperature, and obtaining a zinc-doped hard carbon negative electrode material after cooling.

2. The preparation method according to claim 1, characterized in that: In step 1, the zinc salt is selected from a combination of one or more of zinc acetate, zinc citrate, zinc sulfate, zinc nitrate and zinc perchlorate; Preferably, the solvent is a mixed solvent of deionized water and anhydrous ethanol; preferably, the volume ratio of the two is 1:1; Preferably, in step 1, the mass ratio of the 2,4-diaminophenol to the zinc salt is 3:1 to 10:

1.

3. The preparation method according to claim 1, characterized in that: In step 1, the concentration of 2,4-diaminophenol in the mixed solution is 0.2-0.3 mol / L; Preferably, the concentration of the zinc salt in the mixed solution is 0.02-0.05 mol / L.

4. The preparation method according to claim 1, characterized in that: In step 2, the mass of the formaldehyde solution is 2 / 3 to 1 times the mass of the 2,4-diaminophenol; Preferably, in step 2, the formaldehyde solution is a 30% to 40% formaldehyde aqueous solution; Preferably, in step 2, the temperature for the water bath heating and stirring reaction is 60-70° C. and the reaction time is 2-8 hours; Preferably, the filtration is performed by centrifugation to remove the supernatant; the washing is performed by anhydrous ethanol at least 3 times; Preferably, the drying temperature is 80 to 110° C. and the drying time is 12 to 24 hours.

5. The preparation method according to claim 1, characterized in that: In step 3, the mass of the hard carbon particles is 5 to 40 times that of the zinc salt; Preferably, the high temperature calcination temperature is 900-1500°C, and the calcination time is 1-4h; Preferably, the high-temperature calcination is carried out in an inert gas atmosphere, wherein the inert gas is selected from one or more of argon, helium and nitrogen.

6. A zinc-doped hard carbon negative electrode material, which is prepared by the preparation method according to any one of claims 1 to 5.

7. A method for preparing a pre-sodium / potassium-zinc doped hard carbon negative electrode material, characterized in that: The preparation method comprises the following steps: Step 1, adding degassed mineral oil to a sodium block or a potassium block for ultrasonic pulse heating to dissolve and form liquid sodium; uniformly dispersing the liquid sodium or liquid potassium in the mineral oil by ultrasonic oscillation; further dispersing the substrate obtained by centrifugation in a dimethyl carbonate solution to obtain a DMC-Na or DMC-K solution; Step 2, mixing the zinc-doped hard carbon negative electrode material according to claim 6 with conductive carbon black and sodium carboxymethyl cellulose in an N-methylpyrrolidone solution to obtain a mixed solution, coating the mixed solution on a copper foil, and cutting into zinc-doped hard carbon negative electrode small discs after air drying and vacuum drying again; Step 3, adding DMC-Na or DMC-K solution to the surface of zinc-doped hard carbon negative electrode small disc for diffusion reaction, after DMC-Na or DMC-K solution is completely diffused on the surface of the small disc, a pre-sodium / potassium-zinc doped hard carbon negative electrode material is obtained.

8. The preparation method according to claim 7, characterized in that: In step 1, the mass fraction of the sodium or potassium block in the mineral oil is 0.5% to 1%; Preferably, in step 1, the mineral oil is degassed by ultrasonic method in an inert gas atmosphere; the degassing time is 10 to 30 minutes; the inert gas is selected from one or more of argon, helium and nitrogen; Preferably, in step 1, the ultrasonic pulse heating temperature is 90-110° C., the heating time is 0.5-5 min, the stop time is 10s-60s, the heating-resting times are 10-20 times; and the ultrasonic oscillation time is 5-30 min; Preferably, in step 1, the volume of the N-methylpyrrolidone solution is 0.5 to 0.8 times the volume of the mineral oil; Preferably, in step 2, the mass ratio of the zinc-doped hard carbon negative electrode material to the conductive carbon black and the sodium carboxymethyl cellulose is 8:1:1; the solid content of the mixed solution is 50% to 70%; Preferably, in step 2, the air drying temperature is 80-110° C.; the air drying time is 0.5-3 h; the vacuum drying temperature is 20-30° C.; the vacuum drying time is 1-4 h; Preferably, in step 3, the amount of the DMC-Na or DMC-K solution added is 5 to 15 μL, and the diffusion reaction time is 1 to 5 min.

9. A pre-sodium / potassium-zinc doped hard carbon negative electrode material, which is prepared by the preparation method according to claim 7 or 8.

10. Use of the zinc-doped hard carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 5, or the zinc-doped hard carbon negative electrode material according to claim 6, or the pre-sodium / potassium-zinc doped hard carbon negative electrode material prepared by the preparation method according to claim 7 or 8, or the pre-sodium / potassium-zinc doped hard carbon negative electrode material according to claim 9 in the preparation of sodium ion batteries or potassium ion batteries.